Dynamic risk factors for complex regional pain syndrome after distal radius fracture surgery: multivariate analysis and prediction - Weipan Xu; Yue Liu; Bin Zhang; Junhua Ma (BMC Musculoskeletal Disorders)
Abstract Background Distal radius fractures are a common orthopedic injury, particularly prevalent among elderly and osteoporotic patients. Although surgical treatment effectively restores fracture alignment and stabilizes the bone, Complex Regional Pain Syndrome (CRPS) can occur as a postoperative complication, severely impacting patients’ rehabilitation and quality of life. Therefore, assessing the risk factors for postoperative CRPS is crucial for early clinical intervention, aiming to improve recovery outcomes and overall patient well-being. Objective This study aims to dynamically evaluate the risk factors for CRPS following distal radius fracture surgery through a retrospective analysis. The goal is to provide scientific evidence for early clinical identification and intervention. Methods A retrospective analysis was conducted on 191 adult patients who underwent distal radius fracture surgery between January 2021 and December 2022, comprising 89 males and 102 females, with an average age of 59.7 ± 11.6(18–75) years. Baseline and follow-up data, including demographic information, clinical characteristics, and psychological assessments, were collected. Descriptive statistics, univariate, and multivariate logistic regression analyses were used to identify independent risk factors and assess their dynamic changes over time. Results Age, gender, occupation, fracture type, surgical method, osteoporosis, pain score (VAS), functional disability score (DASH), anxiety score (GAD-7), depression score (PHQ-9), physical therapy, and occupational therapy significantly affected the incidence of CRPS. Age and VAS scores were consistent risk factors. Female gender, internal fixation surgery, and high DASH scores posed higher risks in the early postoperative period but decreased over time. Occupation and fracture type were more significant in the mid to late postoperative period. Psychological factors were most significant in the midterm, while physical and occupational therapy were protective factors early on. Conclusion The occurrence of CRPS is the result of many factors. Elderly patients, females, and manual laborers had higher risks, with complex fractures and internal fixation surgery patients showing increased risk later on. Osteoporotic patients had higher risks in the mid to late postoperative period. VAS, DASH, GAD-7, and PHQ-9 scores were significantly associated with CRPS. Early physical and occupational therapy can effectively prevent CRPS, but further research is needed to evaluate their long-term effects.